Un port rural antique de fond d’estuaire à Blainville-sur-Orne (Calvados) - Cécile Allinne (Gallia)
This tripartite article reports on the state of investigations carried out in a small Roman port in the lower Dan valley, at Blainville-sur-Orne, occupied from the end of the 1st c. AD to the mid-4th c. AD. The general presentation of the site, which is characterised by very loose occupation, constitutes the first part of the text. Firstly, the various areas that make up the site are described: the top of the neighbouring spur, the valley bottom on the southern bank, the buildings on the slope of the northern bank, and lastly the valley bottom on the same side, where the port facilities were located along the Dan river. The ancient port was established in a landscape that differs greatly from the current landscape. A reconstruction of this river environment is proposed, based on paleoenvironmental studies combined with the field investigations: the Dan river formed a shallow body of water, 20 to 30 m wide, 1 km upstream from the confluence with the Orne, which in Roman times opened up into a vast estuary. The port of Blainville-sur-Orne was thus connected to the English Channel. The second part of the article is devoted to a detailed description of the port infrastructures: the stone quay, the quay walls, the foundations of two piers and a submerged slipway. Particular attention is paid to the description of the construction methods and the evolution of these architectural elements. Comparisons with the traditional constructions of dykes and harbour basins on the current banks upstream from the Adour river (Landes) shed light on the understanding of the architecture of the complex, in particular the piers, of which only the foundations were preserved. Their elevations could have been simply composed of compacted earth and embankments, maintained by vegetation. The example in the Landes also proves that these types of constructions were well adapted to a river environment with low activity and subject to the tides, as was the case in the upper part of the ancient estuary of the Orne river. Although they were prone to silting up and were easily destroyed during high floods, they were nevertheless easy to rebuild and required only a few technical and human resources. Lastly, an assessment is proposed of what has been understood about the economic functioning of this trading place, notably thanks to the abundant coin finds. This third part raises the question of the role of the small ports within the local economic networks. A parallel is drawn with a historical situation far from the Roman world, but which makes it possible to evaluate the link between economic development and port architecture: the circulation of goods along the bayous of Louisiana in the 19th c. A keystone of the cotton industry, the collection of the harvests of the plantations was based on a very dense network of small jetties, far away from anywhere else, along the waterways. These infrastructures, notwithstanding their individual modesty, taken as a whole, nevertheless contributed to an extremely dynamic river economy. This last reflection leads us to speculate on the network function of comparable settlements in Blainville-sur-Orne, as well as on the different categories of rural ports that are thought to have existed in Roman times, for example those associated with villae, hamlets, rural settlements, or production sites.